Dancing in the sky a story of hope for grieving hearts - McDonald, Yong Hui V. (Brighton, Colo. : Adora Productions, 2010)
Immobilized with the pain and grief from the loss of her husband of 30 years, Chaplain McDonald experienced an amazing recovery with the help of God. She tells her story of recovery in the hope that others may be helped through their grieving process.
pt. 1. A story of hope for grieving hearts -- pt. 2. Yong Hui's message to Keith's two last congregations -- pt. 3. Keith's last email devotion written on July 9, 2008 -- pt. 4. A life story written by Keith for his funeral -- pt. 5. Youth reflection by Sara Gallegos -- pt. 6. A 30-day prayer project : how to grieve & experience healing from the death and loss of your loved one -- pt. 7. Invitations.
Description based on print version record.
Keywords: Grief; Church work with the bereaved; RELIGION / General; RELIGION / Christian Life / Death, Grief, Bereavement; Electronic books